The Flash by Mark Waid : Book seven - Waid, Mark, 1962- (DC Comics, 2020)
In 1990 Mark Waid's legendary writing career began when he scripted his first issue of The Flash. Waid continued to work on Wally West for nearly a decade, building a world that would keep the character running for years after Waid's departure to other titles. Under Waid's keen pen, Wally West gained a new depth of character that changed The Flash for good. Wally West, Jay Garrick, Max Mercury and Jesse Quick run into a variety of speedsters as they travel the time stream looking to save the lives of future Flashes! Includes Flash #142-150, Flash Secret Files, Speed Force, Flash 80-Page Giant.